Human behavioral assessments in current research of Parkinson's disease. (September 2016) - Asakawa, Tetsuya; Fang, Huan; Sugiyama, Kenji; Nozaki, Takao; Kobayashi, Susumu; Hong, Zhen; Suzuki, Katsuaki; Mori, Norio; Yang, Yilin; Hua, Fei; Ding, Guanghong; Wen, Guoqiang; et al.
Highlights: Assessments should include motor- and non-motor symptoms. Assessments covering Human patients were discussed. Bias should be avoided during the experimental design. Principles of OMS are important in the experimental design for Human behavioral assessments. Improving the assessments for non-motor symptoms in PD patients was emphasized. Abstract: Parkinson's disease (PD) is traditionally classified as a movement disorder because patients mainly complain about motor symptoms. Recently, non-motor symptoms of PD have been recognized by clinicians and scientists as early signs of PD, and they are detrimental factors in the quality of life in advanced PD patients. It is crucial to comprehensively understand the essence of behavioral assessments, from the simplest measurement of certain symptoms to complex neuropsychological tasks. We have recently reviewed behavioral assessments in PD research with animal models (Asakawa et al., 2016). As a companion volume, this article will systematically review the behavioral assessments of motor and non-motor PD symptoms of human patients in current research. The major aims of this article are: (1) promoting a comparative understanding of various behavioral assessments in terms of the principle and measuring indexes; (2) addressing the major strengths and weaknesses of these behavioral assessments for a better selection of tasks/tests in order to avoid biased conclusions due to inappropriate assessments; and (3) presenting new concepts regarding the development of wearable devices and mobile internet in future assessments. In conclusion we emphasize the importance of improving the assessments for non-motor symptoms because of their complex and unique mechanisms in human PD brains.